Strategi Guru Dalam Mengenalkan Media Digital Kepada Anak Kelompok A Tk It Insan Mulia Kabupaten Wonosobo - Rahma Susanti, Maulida; Kesuna Hilyati Fadhila; Istiqomah; Dita Nurul Istiqomah; Fatkhurrohman (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
The development of technology has a significant impact on various aspects of life, including in the field of education to the lowest level of education, namely early childhood education. It is important for teachers to develop the right strategy in the use of digital media in early childhood. Through strategies that have been prepared by the teacher, children can get how to use digital media well. This study aims to determine the teacher's strategy in introducing digital media to group A children at Insan Mulia IT Kindergarten, Wonosobo Regency. In this study, the author uses qualitative research methodology with data obtained from interviews and some documentation from TK IT Insan Mulia, Wonosobo Regency. Based on the research that has been done, the results of the study show that in carrying out learning teachers have planned lessons that have been compiled in RPPH. Teachers introduce digital media to the topic of learning communication tools, but in the use of almost all learning topics using digital media. Digital media used are digital devices that are around children such as laptops, PCs, mobile phones and projectors. In the implementation of learning using digital media is also carried out to teach digital literacy to children, besides that teachers also involve parents. This form of assessment in learning states that there is no specific assessment but assessment is included in the use of digital media to support learning. There are supporting factors including adequate infrastructure, teacher competence, and support from parents. Of course, there are obstacles in the implementation of learning, namely different backgrounds of children.